Wireless Penetration Testing Method To Analyze WPA2-PSK System Security And Captive Portal - Wahyudi, Erfan; Efendi, Muhammad Masjun (STMIK Mataram, 2019)
One of the major changes in the telecommunications sector is the use of wireless technology. But many problems that must be faced when implementing this wireless network, one of which is a security problem. Many people are still questioning about wireless security, and many others believe that wireless security systems using WPA2-PSK are more secure than other wireless security systems. However, based on the results of literature studies conducted, a wireless security system that really can provide more secure security is to use the system security Remote Authentication Dial-In User Servers (RADIUS) server. While at present, many parties still use WPA2-PSK as their wireless security system to avoid the possibility of unauthorized use of internet access by unauthorized people. This study aims to analyze the comparison of the two wireless network security systems above. The test was performed using wireless penetration testing method, and the result stated that 80% of Security Captive Portal system is more secure than WPA2-PSK.